Tumor necrosis factor-alpha (TNF-alpha)-238 G/A polymorphism is associated with the treatment resistance and attempted suicide in schizophrenia - Aytaç, Hasan Mervan; Özdilli, Kürşat; Tuncel, Fatıma Ceren; Pehlivan, Mustafa; Pehlivan, Sacide (Taylor & Francis Ltd, 2022)
Abnormality of the immune system may play an important role in the pathogenesis of schizophrenia (SCZ). We aim to investigate the relationship between clinical features of SCZ and tumor necrosis factor-alpha (TNF-?) -238 G/A, -308 G/A polymorphisms in SCZ patients by comparing genotype distributions of TNF-? gene polymorphisms between patients and healthy controls. A sample of 113 patients with SCZ and 104 healthy volunteers was included in the study. SCID-I was used to confirming the diagnosis according to DSM-IV-TR criteria. We evaluated the patients with some scales and data forms in terms of clinical features, symptom severity, level of insight, suicidal behavior, and treatment response. PCR-RFLP was used to determine TNF-? gene polymorphisms from DNA material. The distributions of TNF-? - 238 G/A and TNF-? - 308 G/A polymorphisms of the patients diagnosed with SCZ were not significantly different from the control group. There was a significant difference in the TNF-? - 238 G/A genotype distributions between treatment-resistant and treatment-responsive SCZ patients. Again, the distributions of TNF-? - 238 G/A genotype of attempted suicide patients in SCZ were significantly different from the non-attempted suicide of SCZ patients. Whereas TNF-? - 238 G/A and -308 G/A polymorphisms were not associated with SCZ, TNF-? - 238 G/A polymorphism may be related to treatment resistance and attempted suicide in SCZ patients in the Turkish population.
Tumor necrosis factor-alpha (TNF-?) ?238 G/A polymorphism ıs associated with the treatment resistance and attempted suicide in schizophrenia
Keywords: Schizophrenia; Attempted Suicide; Single Nucleotide Polymorphism; Tnf-a; Treatment Resistance